Modeling of the process of kneading the yeast dough by modern working elements - Rachok, Vitalii; Telychkun, Volodymyr; Telychkun, Yuliia (My University, 2019)
The scheme of the mathematical modeling of the process of mixing of the yeast dough in a dough machine of continuous action is developed. Based on the results of simulation of the mixing process, cam operating elements, the distribution of strain of displacement and dissipation of yeast dough in the working chamber were obtained. As the angle of the position of the cam element increases on the shaft, there is an increase in the shear stress. The greatest indices of shear stress occur in the area of cam clamping elements and in the contact area of the cam with the walls of the case, numerical values reach within 7000-8000 Pa. For the rest of the camera, the displacement stress reaches 1000-3000 Pa. Distribution of dissipation shows that in parts of the working chamber here is the formation of heat in the area of flow. With the increase of the angle of the cam of the cam element, there is a gradual increase in temperature. At the site of mixing 12 pairs of cams, the temperature of the yeast dough increases by almost 5° C. Taking into account that before the simulation, the initial temperature reached t=30° C, and upon completion of the mixing process did not exceed 35° С, the pastry preparation parameters were observed. The greatest heat release occurs in the area of the cam clamping elements. The results of mathematical modeling are confirmed by physical experiments on a test dough mixing machine of continuous action, an error within 5%
Keywords: dough; dissipation; kneading; cam; modeling; rotation; тісто; розсіювання; замішування; кулачок; моделювання; обертання; кафедра машин і апаратів харчових та фармацевтичних виробництв